REVIEW ARTICLE-GREEN STRATEGIC COST MANAGEMENT TECHNIQUES IN THE MODERN MANUFACTURING LANDSCAPE (World Economics and Finance Bulletin, 2025)
This article seeks to highlight and review modern technologies, including strategic costing tools. It discusses and reviews some studies and research related to these technologies, which contribute to the production of high-quality products at a low cost. It also discusses how to classify these technologies and divide them into technologies that focus on inventory, such as just-in-time production; technologies that focus on budgeting, such as activity-based costing; technologies that focus on product design stages, such as target costing; and technologies that focus on improving the economic unit, such as benchmarking, by comparing the performance of the economic unit with leading units in its field. It adopts and demonstrates the most important scientific and cognitive foundations of these technologies. The importance of this article is highlighted by the role these technologies play in the transition towards sustainability, zero inventory, and green production. Therefore, companies and institutions must make the most of strategic costing tools to rationalize investment decisions in the modern manufacturing environment by adopting comprehensive and flexible evaluation methods that take into account market fluctuations, changes, and uncertainties, with the aim of achieving a competitive advantage and achieving sustainable profits in the long term
Keywords: Green Strategic Cost Management Techniques; Just-In-Time; Benchmarking technique